1688c The contribution of task- and worker-related accommodation to asthenopia: a critical literature review. (24th April 2018) - Piccoli, Bruno; Pisaniello, Dino; Colais, Letizia; Gaskin, Sharyn; D'Orso, Marco
Abstract : Introduction: Near work is believed to be a key factor in the development of occupational asthenopia as well as being a possible cofactor for the development of adult myopia. Prolonged viewing distances of less than one metre induce visual symptoms by imposing a sustained contraction of ciliary muscles. Small screens on mobile devices are very common in modern work environments, and there are many jobs and tasks that require near work every day. Furthermore, there is an ageing workforce where there is less capacity for visual accommodation. This review critically assesses the published literature on asthenopia attributable to task observation distance and worker-related accommodative capacity. Methods: A systematic search of PubMed, Scopus, and Embase was used, and supplemented with forwards, backwards and hand-searching, including by author. The major search terms were 'observation distance', 'near work' and 'visual work load'. Results: Most published papers reporting on asthenopia in the workplace classify visual effort in broad terms, without objective 'on site' measurement of task-determined visual distances/durations. Similarly, few papers separately consider workers over 45 (presbyopia), and those who are long sighted (hyperopia), where there is a greater requirement of accommodation compared to normal sighted (emmetropes). Even fewer papers juxtapose the observation distance with the worker capacity for accommodation, i.e. combining exposure and susceptibility, which is essential for the characterisation of asthenopia risk. Discussion: In order to assess and manage risks for asthenopia attributable to visual effort, equal weight should be given to task and individual factors. Future studies should utilise objective measurements of task viewing distance and durations. Currently, there is a need for a personal monitoring device that can continuously measure and datalog these parameters. With regard to an ageing workforce, intervention research is needed to determine whether the provision of larger screens, larger images and less visual demanding software reduces asthenopia.